Patterns, Causes, and Mortality Trends of Road Traffic Accidents in Hamedan Province, Iran: A Spatiotemporal Epidemiological Analysis (2011-2024). - Jalili, Ebrahim; Khazaei, Salman; Khazaei, Mahdi; Omidi, Sanaz (Journal of Research in Health Sciences)
Background: Road traffic accidents (RTAs) are a major cause of death, especially in developing countries. This study analyzed RTA patterns and trends in Hamadan province, Iran, from 2011 to 2024. Study Design: A cross-sectional study. Methods: Data on 6,488 road traffic fatalities, excluding non-road transport deaths, were obtained from the Forensic Medicine Organization. Demographics, injury type, location, and mode of transport were analyzed. Then, spatial clustering was performed using the K-prototype algorithm, with cluster quality assessed via the Silhouette Score. Finally, mortality trends were forecasted using the Prophet model with 95% prediction intervals and evaluated using RMSE, MAE, MASE, and MAPE. Results: The mean age of victims was 49 ± 21 years, with most deaths observed in the 15--44 age group. Most victims were male (75%), urban residents (60%), married (69%), and had not completed secondary education (41%). Fatalities mainly occurred at the scene (48%) or en route to the hospital (43%), with head/face injuries and hemorrhage as the leading causes. Spatial analysis revealed three clusters, with Famenin having the highest mortality (73.7 per 100,000). Mortality was projected to decline from 18.27 (16.01, 20.55) in 2025 to 9.57 (7.37, 11.69) in 2028, rising slightly to 13.94 (11.83, 16.17) in 2029. Conclusion: Overall, the findings emphasize the need for targeted regional interventions (e.g., road safety education, enhanced emergency services, and infrastructure upgrades) to reduce RTA mortality in the high-risk areas of Hamedan Province.